A potent drug candidature of Cu(II) pyrazino[2,3-f][1,10]phenanthroline complexes with bioactive ligands: synthesis, crystal structures, biomolecular interactions, radical scavenging and cytotoxicities - Inci, Duygu; Aydin, Rahmiye; Vatan, Ozgur; Zorlu, Yunus (Taylor & Francis Inc, 2021)
A novel ternary copper(II) complexes, - [Cu(py-phen)(asn)(NO3)(H2O)] (1) and [Cu(py-phen)(trp)(H2O)]NO3(2)- (py-phen: pyrazino[2,3-f][1,10]phenanthroline, asn: asparagine, trp: tryptophan), have been synthesized and characterized by CHN analysis, ESI-MS, FTIR and single-crystal X-ray diffraction techniques. Interaction of the complexes1and2with CT-DNA has been investigated by absorption spectral titration, EB and Hoechst 33258 displacement assay. The interaction between the complexes1and2and BSA was investigated by electronic absorption and fluorescence spectroscopy methods. The experimental outcomes indicate that the fluorescence quenching mechanism between the complexes1and2and BSA is a static quenching process. The Stern-Volmer constants, binding constants, binding sites and the corresponding thermodynamic parameters (Delta G, Delta H, Delta S) of BSA + complex systems were determined at different temperatures. The binding distance between the complexes1and2and BSA was calculated according to FRET. The effect of the complexes1and2on the conformation of BSA was also examined using synchronous, two dimensional (2D) and three dimensional (3D) fluorescence spectroscopy. Radical scavenging activity of the complex was determined in terms of EC50, using the DPPH and H(2)O(2)method. The anticancer activities of the complexes1and2were investigated using an XTT assay against three cancer cell lines (MCF-7, Caco-2 and A549) and non-tumor cell line (BEAS-2B). A potent drug candidature of two new copper(II) complexes, - [Cu(py-phen)(asn)(NO3)(H2O)] (1) and [Cu(py-phen)(trp)(H2O)]NO3(2)- (py-phen: pyrazino[2,3-f][1,10]phenanthroline, asn: asparagine, trp: tryptophan), have been synthesized and characterized by CHN analysis, FTIR, ESI-MS and single-crystal X-ray diffraction techniques. The complexes have been tested for theirin vitrobiomolecular interactions by the spectroscopic methods. Furthermore, radical scavenging and anticancer activities of the complexes was also investigated.
Keywords: Cu(II); pyrazino[2; 3-f][1; 10]phenanthroline; amino acids; biomolecular interactions; radical scavenging activity; anticancer activity